2016
DOI: 10.1155/2016/5675739
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 Serum Levels and Adiposity Are Associated with the Polymorphic Phenotypes -2518A on CCL2 and 64ILE on CCR2 in a Mexican Population with Insulin Resistance

Abstract: Genetic susceptibility has been described in insulin resistance (IR). Chemokine (C-C motif) ligand-2 (CCL2) is overexpressed in white adipose tissue and is the ligand of C-C motif receptor-2 (CCR2). The CCL2 G-2518A polymorphism is known to regulate gene expression, whereas the physiological effects of the CCR2Val64Ile polymorphism are unknown. The aim of the study is to investigate the relationship between these polymorphisms with soluble CCL2 levels (sCCL2), metabolic markers, and adiposity. In a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…26 In another context, we have previously reported frequencies of IR of 39% in individuals with excess of weight 2 and 62% in individuals with obesity in our population aged 20-59 years; 27 this cohort also included 31.3% of individuals with dyslipidemias. 28 These frequencies are in agreement with the group included for this study, and in which, risk factors for the development of IR were identified.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…26 In another context, we have previously reported frequencies of IR of 39% in individuals with excess of weight 2 and 62% in individuals with obesity in our population aged 20-59 years; 27 this cohort also included 31.3% of individuals with dyslipidemias. 28 These frequencies are in agreement with the group included for this study, and in which, risk factors for the development of IR were identified.…”
Section: Discussionsupporting
confidence: 88%
“…Our previous works also show similar lipid profile and no differences in HDLc levels in our population with IR versus without IR. 2,27,28 Amid of this fact, it was not possible to establish the clinical relationship between the circulating levels of the miR-33 family and HDLc.…”
Section: Discussionmentioning
confidence: 99%
“…interferon (IFN)-γ) or by pathogen-associated molecular patterns (PAMPs) (i.e. LPS) and is characterized by the production of pro-inflammatory cytokines (IL-6, TNF-α, IFN-γ, IL-1β, IL-12 and IL-23), chemokines promoting inflammatory infiltrate (CXCL9, 10,11,13,CCL8,15,19,20), and expressed on surface high levels of MHCII, CD80, CD86 and CD11c, among other markers (i.e. Ly6C, CD11b, CD62L, CCR2, CX3CR1 and CCR5).…”
Section: Macrophagesmentioning
confidence: 99%
“…Metabolic diseases Reference IL-4 promoter polymorphism (IL-4 C-589T and C-34T) Type 2 diabetes (Ho et al, 2010) IL-4 promoter polymorphism (IL-4-589 C/C) Lower circulatory high-density lipoprotein cholesterol level (HDL-C) (Ho et al, 2010) IL-4Rα polymorphism (IL-4Rα E400A) Dysfunction of lipid metabolism (Chang et al, 2012) IL-4Rα haplotypes Type 1 diabetes (Mirel et al, 2002) IL-4Rα, IL-4 and IL-13 loci Type 1 diabetes (Bugawan et al, 2003) IL-4 locus Type 2 diabetes (Ban et al, 2010) IL-6 single nucleotide polymorphism (IL-6C-174G) Type 2 diabetes (Illig et al, 2005) CCL2 and CCR2 polymorphism (CCL2 G-2518A), CCR2 (Val64Ile) Insulin resistance (Guzman-Ornelas et al, 2016) SNPs and haplotypes in TLR1 and TLR6 Type 1 diabetes (Sun et al, 2014) TLR4 variants High TC/HDL-C (Kolz et al, 2008) ing in response to the cold challenge or hormonal stimulation (Hui et al, 2015;Qiu et al, 2014). In accordance, elevated production of meteorin-like protein (Metrnl) in adipose tissue upon cold exposure and in muscle after exercise training, was recently shown to exert beneficial effects upon energy expenditure, adipose inflammation, and glucose metabolism through inducing the production of eosinophil-derived IL-4, which could in turn promote the M2 activation of ATMs and browning of scWAT (Rao et al, 2014).…”
Section: Genesmentioning
confidence: 99%